2001
DOI: 10.1073/pnas.111144998
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for clonal propagation in natural isolates of Plasmodium falciparum from Venezuela

Abstract: We have analyzed 75 isolates of Plasmodium falciparum, collected in Venezuela during both the dry (November) and rainy (May-July) seasons, with a range of genetic markers including antigen genes and 14 random amplified polymorphic DNA (RAPD) primers. Thirteen P. falciparum stocks from Kenya and four other Plasmodium species are included in the analysis for comparison. Cross-hybridization shows that the 14 RAPD primers reveal 14 separate regions of the parasite's genome. The P. falciparum isolates are a monophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
3
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 48 publications
0
29
3
2
Order By: Relevance
“…The inference followed that "uniparental and biparental lineages may coexist within this species, for which a sexual cycle has been a classical notion" (Tibayrenc et al, 1990). Although this inference was corroborated by further studies (Ben Abderrazak et al, 1999;Urdaneta et al, 2001), it resulted in a vehement outcry (Dye et al, 1990;Walliker, 1991;Walliker et al, 1990). Our proposal was widely rejected.…”
Section: Initial Proposalsmentioning
confidence: 79%
“…The inference followed that "uniparental and biparental lineages may coexist within this species, for which a sexual cycle has been a classical notion" (Tibayrenc et al, 1990). Although this inference was corroborated by further studies (Ben Abderrazak et al, 1999;Urdaneta et al, 2001), it resulted in a vehement outcry (Dye et al, 1990;Walliker, 1991;Walliker et al, 1990). Our proposal was widely rejected.…”
Section: Initial Proposalsmentioning
confidence: 79%
“…Anderson et al (5) observed significant linkage disequilibrium among 12 microsatellite loci in all localities with low infectivity and in two of five populations from regions with high transmission frequencies. Other results have been interpreted as indicating that P. falciparum reproduction may be genetically clonal in low-infectivity regions but predominantly panmictic in high-infectivity regions (13,14). Nevertheless, Durand et al (30) found significant linkage disequilibrium in two African populations from the Republic of the Congo, where infectivity is high.…”
Section: Discussionmentioning
confidence: 91%
“…The incidence of clonality or inbreeding versus outbreeding or panmixia is estimated indirectly by measuring genetic diversity, linkage disequilibrium, and the like (2,6,(8)(9)(10)(11)(12)(13)(14)(15)(16). Hence the conflicting evidence favoring different levels of clonality or panmixia, although it is often accepted that P. falciparum displays different population structures in different places, ranging from clonality to panmixia in approximate correlation with the increasing intensity of transmission (2,5,6,(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…The extent of cross-fertilization and panmixia relative to clonal reproduction in P. falciparum has indeed been the subject of considerable debate during the last decade (13,19,(26)(27)(28)(29)(30). The current consensus is that this parasite species displays a range of population structures associated with the levels of transmission intensity (13).…”
Section: Discussionmentioning
confidence: 99%